2014
DOI: 10.1111/all.12447
|View full text |Cite
|
Sign up to set email alerts
|

The relation of airway obstruction to asthma, chronic rhinosinusitis and age: results from a population survey of adults

Abstract: RationaleThere is conflicting evidence on whether patients with asthma experience an accelerated decline in lung function with age. We examined the association between postbronchodilator lung function, asthma, chronic rhinosinusitis (CRS), and atopy with age using a large European sample.MethodsIn 17 centers in 11 European countries, case–control studies were nested within representative cross-sectional surveys of adults aged less than 75 years. Representative samples of participants with asthma, CRS or both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The important finding of this study is that when people who reported ever being diagnosed with asthma were excluded, there was no association between atopy and post‐bronchodilator airflow limitation in the remaining population. This is consistent with a more recent meta‐analysis of a European multicentre study that demonstrated that participants with atopy did not have lower lung function …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The important finding of this study is that when people who reported ever being diagnosed with asthma were excluded, there was no association between atopy and post‐bronchodilator airflow limitation in the remaining population. This is consistent with a more recent meta‐analysis of a European multicentre study that demonstrated that participants with atopy did not have lower lung function …”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a more recent meta-analysis of a European multicentre study that demonstrated that participants with atopy did not have lower lung function. 23 Earlier studies had reported that when asthma was excluded, allergic sensitization was not associated with airflow limitation. 2,3,9 However, these studies did not measure post-bronchodilator airflow obstruction, and hence could have been confounded by factors leading to transient bronchoconstriction, including triggers for asthma.…”
Section: Discussionmentioning
confidence: 98%
“…By use of self-reported information, individuals in remission who reported ever asthma at baseline may have been mild cases without symptoms at follow up. Furthermore, we may have overestimated the number of cases of COPD by using the LLN by the 5th percentile of FEV₁/FVC corresponding to z-score <−1.64, and the relatively low dose of beta-agonist chosen due to the study setting in a general population [39]. The use of two different kinds of spirometers, one with a turbine (MicroLoop) at baseline and one with ultra-sound transit time measurement (ndd EasyOne) at follow up may have affected the lung function data although calibration check was performed daily on both spirometers to minimise this bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, measuring PEF together with PNIF in rhinologic patients is easy and, as mentioned above, interesting because it translates the current thinking of a single airway disease in which signs of disease in one part of the respiratory tract should be considered as a disease of the whole in an integrated fashion, allowing to have a more reliable idea of patients’ airways condition. Furthermore, as a moderate correlation between PNIF and PEF has also been demonstrated in children and adolescents, and PEF is predictive and informative of PNIF also in this population, low values of PNIF should be always confirmed by PEF to exclude a reduction in lower airway patency .…”
Section: The Relation Between Nasal Flow and Patency Measurements Andmentioning
confidence: 99%